2010
DOI: 10.1111/j.1651-2227.2010.01890.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of diet on total antioxidant status, ceruloplasmin, transferrin and ferritin serum levels in phenylketonuric children

Abstract: The low ferritin levels found in 'off diet' patients with PKU may be attributed to a decreased liver production of ceruloplasmin, which evaluation may be a useful tool for the follow-up of patients with PKU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…However, this relationship was not established in the nonobese group. Schulpis KH et al 2010 reported that, obesity has been associated with iron deficiency in overweight children and adolescents, as well as in obese adults. It was also reported that cells enriched by ferritin showed an enhanced resistance to oxidative stress, whereas cells in which ferritin was down regulated had reduced resistance to oxidative stress (Schulpis et al 2010).…”
Section: Clinical Characteristics Of the Participantsmentioning
confidence: 99%
“…However, this relationship was not established in the nonobese group. Schulpis KH et al 2010 reported that, obesity has been associated with iron deficiency in overweight children and adolescents, as well as in obese adults. It was also reported that cells enriched by ferritin showed an enhanced resistance to oxidative stress, whereas cells in which ferritin was down regulated had reduced resistance to oxidative stress (Schulpis et al 2010).…”
Section: Clinical Characteristics Of the Participantsmentioning
confidence: 99%
“…Accordingly, reduced plasma β-carotene in PKU patients has been reported to negatively correlate with serum Phe levels (Sanayama et al 2011). The adherence to the PKU diet is usually related to a higher total plasma antioxidant status and a reduced lipid ingestion with increased proportion of polyunsaturated fat (Schulpis et al 2003(Schulpis et al , 2010. In other words, it is important to advise PKU patients that diet may offer other advantages besides management of Phe levels (Schulpis et al 2003, Schulpis et al 2005, Schulpis et al 2007.…”
Section: Oxidative Stress Data In Pku Patientsmentioning
confidence: 99%
“…These data are not included in this table. The data for all PKU patients from these publications were pooled for the meta-analysis d For all studies by Schulpis et al [ 124 128 , 136 ], the PKU group was sub-grouped into well controlled PKU and poorly controlled PKU. Differences between well-controlled PKU and healthy controls only are reported in this table.…”
Section: Resultsmentioning
confidence: 99%